2017
DOI: 10.1016/j.future.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Static analysis of Taverna workflows to predict provenance patterns

Abstract: Workflows have found adoption in scientific domains particularly due to their automation and provenance features. Using workflows scientists can repeat analyses with different input parameters to later use provenance to access and compare results based on respective parameters. An assumption that is often made is that by designing an analysis as a workflow, we get parameterto-result traceability for free with workflow provenance. This assumption holds for cases of coarse-grained traceability, where an entire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In prior work we've tackled this problem and shown that workflows can be analyzed to check whether their provenance will have the n-by-m pattern, i.e., lack of discrete traceability [31]. We find it important to highlight this pattern in the context of this paper, because, as we shall see in Section 6 if it exists in provenance it equally reduces provenance utility even after labelling.…”
Section: Our Case Highlights the Following Issuesmentioning
confidence: 98%
See 3 more Smart Citations
“…In prior work we've tackled this problem and shown that workflows can be analyzed to check whether their provenance will have the n-by-m pattern, i.e., lack of discrete traceability [31]. We find it important to highlight this pattern in the context of this paper, because, as we shall see in Section 6 if it exists in provenance it equally reduces provenance utility even after labelling.…”
Section: Our Case Highlights the Following Issuesmentioning
confidence: 98%
“…Here we skip the details of Taverna iteration [31], as it is beyond the scope of our work. However, iteration does have an impact on annotation and reporting, which we summarise as follows:…”
Section: Layers Of Provenancementioning
confidence: 99%
See 2 more Smart Citations
“…link the recorded traces with the high-level concepts and the data properties that are specific to their field. Moreover, lack in precision in describing data derivations could make traceability of results ineffective for a correct understanding of the method's behaviour [6]. This suggests the need for linage recording mechanisms that facilitate the contextualisation of the provenance with metadata linking to the purpose of the study.…”
Section: Introductionmentioning
confidence: 99%